PERAN LEMBAGA ADAT KAMPUNG DALAM PEMBERDAYAAN PEREMPUAN DI KABUPATEN SIAK BERDASARKAN PERATURAN DAERAH NOMOR 2 TAHUN 2015 TENTANG PENETAPAN KAMPUNG ADAT KABUPATEN SIAK - Fauziah Nelfi Oktaveni; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia consists of various tribes and cultures that develop as well as diverse customs and are passed down from generation to generation. At the beginning of the formation of this LAM, it was under the auspices of the Education Office and the structure regarding the field of women's empowerment already existed, such activities as merisik, sending rings, delivering shopping, ma'andam accompanied by fresh flour, there was a weaving briefing. However, since 2015 until now, LAM has not had any activities due to the lack of funds.This research is juridical empirical/sociological research, research conducted by linking law to efforts to achieve goals and fulfill concrete needs in society. The approach taken includes a survey approach, which is to go directly to the research location. The type of data used is descriptive data, namely what the respondents stated in writing or verbally and real behavior. The theory used in this research is the theory of legal politics and the theory of state institutions.From the results of this study there are three main things that can be concluded where the role of traditional institutions in increasing women's empowerment for the development and preservation of culture, where the role of women is very influential. One of the duties of traditional institutions is to develop local cultural values in order to enrich, preserve and develop national culture. The main obstacle for Traditional Institutions is in the unclear funding source and resulting in activities not running as usual, this affects the empowerment of women in the Siak Regency area. The efforts of the Kampung Adat Institution in empowering women are the government's attention to institutions and the Regional Regulations governing the Riau Malay Customary Institutions in Siak Regency, especially in empowering women.Keywords: Role, Lam, Women's Empowerment, Traditional Village